The Importance of Renewable Energy for Sustainable Development in Dukuh Papringan, Yogyakarta - Sari, Maya; Purboseno, Sentot (ARRUS Journal of Engineering and Technology, 2024)
Dukuh Papringan, Sleman, Yogyakarta, is an urban area predominantly inhabited by university students from various institutions. These students hold a strategic role in promoting the adoption of renewable energy to reduce dependence on fossil fuels, which leads to high energy costs and significant carbon emissions. This study aims to analyze the potential of renewable energy in Dukuh Papringan, its economic, social, and environmental benefits, and the role of students in supporting the implementation of clean energy technologies. The research employs a qualitative approach through interviews, field observations, and secondary document analysis. The findings indicate that Dukuh Papringan has significant solar energy potential, with an average radiation of 4.8–5.5 kWh/m²/day, along with opportunities for organic waste processing into biogas. The implementation of renewable energy technologies can reduce energy costs by up to 30% and carbon emissions by 40%. Students act as educational agents, initiators of community projects, and researchers in clean energy technology innovation. The success of renewable energy adoption requires synergistic support from the government, universities, and the private sector. Dukuh Papringan has the potential to serve as a model for sustainable energy management in urban areas, contributing to national targets for carbon emission reduction and accelerating the transition to clean energy.